Glycaemic index: Glycaemic load and exercise performance - O'Reilly, J.; Wong, S. H. S.; Chen, Y. (Sports Medicine, 2010)
The concept of the glycaemic index (GI) was first introduced in the early 1980s as a method of functionally ranking carbohydrate foods based on their actual postprandial blood glucose response compared with a reference food (either glucose or white bread). Although the GI is a debatable topic among many exercise and health professionals, nutritional recommendations to improve exercise performance and enhance exercise capacity are regularly based on information related to the GI.